14C characteristics of dissolved lignin along a forest soil profile. (August 2019) - Jia, Juan; Feng, Xiaojuan; Graf Pannatier, Elisabeth; Wacker, Lukas; McIntyre, Cameron; van der Voort, Tessa; Montlucon, Daniel; Eglinton, Timothy
Abstract: Lignin is a key component of soil dissolved organic carbon (DOC) and is recently suggested to track 14 C-young DOC components. However, direct evidence is still lacking to prove this hypothesis in the soil. Here, utilizing molecular radiocarbon dating, we present the first 14 C dataset on dissolved lignin through a Podzol soil profile. Dissolved lignin and hydroxy phenols had similar 14 C content as soil organic carbon (SOC) and DOC in the surface organic layer. However, in contrast to SOC, both DOC and dissolved lignin phenols exhibited consistent and higher Δ 14 C values in the mineral soils. Coupled with lignin phenol concentration data, our results suggest that dissolved lignin comprises a key DOC component throughout this Podzol profile and is mainly supplied by surface leachates with young 14 C ages. Graphical abstract: Image 1 Highlights: We present the first 14 C dataset on dissolved lignin along a Podzol profile. Dissolved phenols exhibited similar Δ 14 C values to SOC and DOC in surface organic layer. Unlike SOC, DOC and dissolved lignin were enriched in 14 C in mineral soils. Surface leachate was the main source of DOC components in this Podzol profile. Dissolved lignin may exhibit larger 14 C variability in other (non-Podzol) profiles.